(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the role of digital financial instruments in stimulating economic growth. It analyzes key technologies, including blockchain, artificial intelligence, and mobile payment systems, and assesses their impact on the accessibility of financial services and the efficiency of financial operations. The study substantiates that the digitalization of the financial sector contributes to reducing transaction costs, fostering innovative business models, and attracting investment.